Conflict and integration of spatial attention between disconnected hemispheres - Ishiai, S (BMJ Group, 2001)
OBJECTIVES—To clarify how the disconnected hemispheres perceive a line and bisect it with successful or unsuccessful integration of spatial attention. METHODS—Eye movements were recorded when a patient with an extensive callosa infarction bisected horizontal lines. The lesion extended into the left cingulate gyrus. RESULTS—When the patient bisected lines with the right hand, the gaze was initially directed rightward and shifted further to the right side with the execution of manual response, which resulted in rightward errors. Shortly after bisection, rapid ocular searches occurred to the left side, whereas the rightward errors did not decrease throughout the trials. When using the left hand, there was no deviation of the gaze before presentation of lines. In the first few trials, the patient bisected the line with a leftward error and then searched rapidly to the right side. The subsequent bisections were almost accurate, as the subjective midpoint was placed near the point of the initial fixation that fell around the true centre. Ocular searching was mostly absent during and after line bisection. CONCLUSIONS—In callosa disconnection, left unilateral spatial neglect may appear when use of the right hand induces a rightward bias in the attentional control of the left hemisphere and damage to its cingulate gyrus inhibits interhemispheric integration of attention. Resultant rightward errors of line bisection often cause interhemispheric conflict of attention, as the right hemisphere perceives the longer extent on the left side. By contrast, the disconnected but intact right hemisphere may bisect a line accurately by integrating attention to the extents perceived in the left and right visual fields.